Studi Kasus: Penerapan Terapi SEFT (Spiritual Emotional Freedom Technique) terhadap Nyeri Pasien dengan Mioma Uteri - Reztika Cahyani; Erika Erika; Henny Yuliawati (Viva Medika, 2023)
Myoma uteri namely Benign tumors of the uterus, apart from being malignant, benign tumors of the uterus or uterine myomas often appear. Types of surgery on uterine fibroids include hysterectomy and myomectomy. This procedure has the potential to be painful. Nursing care for Mrs. S patients with uterine fibroids with acute pain through the SEFT (Spiritual Emotional Freedom Technique) therapy approach were carried out from assessment, diagnosis, nursing plan, implementation to nursing evaluation. The general intervention given is pain management according to the Indonesian Nursing Intervention Standards with acute pain. The pain management intervention was then associated with SEFT non-pharmacological therapy. The SEFT method is a healing method of doing beats at certain meridian points by using the stages of tune-in, set-up, and tapping. After being given the intervention for 3 days, it showed that giving SEFT could reduce the intensity of the pain scale. SEFT therapy can make patients feel calm, comfortable and relaxed so that it affects the pain response. The results of the application SEFT to nursing care, it is recommended that maternity nurses, families and patients be able to practice SEFT therapy in the management of post-op laparotomy and hysterectomy pain patients.